CROP INSURANCE AS PROTECTION FOR FARMERS: A STUDY OF NORMS AND PRACTICES IN INDONESIA - Elisatris Gultom; Manisha Ramadanni; Ramalinggam Rajamanickam (Indonesia Private Law Review, 2026)
Indonesia’s agricultural sector remains dominated by traditional rice farming that contributes modestly to GDP, while farmers face rising risks of crop failure due to climate change and other external factors. This condition reveals a gap between the legal objective of farmer protection and empowerment and the practical effectiveness of crop insurance through the Rice Farming Insurance Program (Asuransi Usaha Tani Padi/AUTP). This article examines whether AUTP constitutes a legally valid general insurance contract under Indonesian civil and commercial law and assesses its effectiveness as a protection mechanism for rice farmers. Using a normative juridical method based on secondary data, the study applies statutory, conceptual, and case approaches to analyze AUTP regulations in relation to empirical findings from prior research. The results indicate that AUTP fulfills the essential elements of loss insurance and qualifies as an innominate contract under Article 1319 of the Civil Code in conjunction with Articles 246 and 247 of the Commercial Code. However, its practical effectiveness remains limited due to internal constraints, including low insurance literacy, premium affordability, and participation rates, as well as external constraints related to institutional capacity, claim mechanisms, and climate-related production risks. These findings suggest that further strengthening of AUTP’s implementation design is necessary to achieve effective farmer protection.